Scattering from chiral cylinders of arbitrary cross-sections above a ground plane - Altaf, Ahsan; Sajjad, Hassan; Özzaim, Cengiz; Arvas, Ercüment (IEEE-Institute of Electrical and Electronics Engineers Inc, 2021)
The main purpose of this work is to solve the problem of electromagnetic scattering from a chiral cylinder of arbitrary cross-section above an infinite perfect electric conducting (PEC) plane. Using image theory, this problem is reduced to two chiral cylinders in free-space. Surface equivalence principle is used to obtain three different equivalent problems for this two-cylinder problem. Then, the method of moments is used to solve these equivalent problems numerically. It is known that the image of a chiral body through a ground plane is another chiral body with the same permittivity and permeability but opposite chirality. Using this property, the two-body problem in the moment method may be reduced to a one-body problem with a complicated moment matrix. Computed numerical results include scattered fields and equivalent surface currents on the cylinder.
Keywords: Surface Waves; Method of Moments; Magnetic Resonance Imaging; Integral Equations; Electromagnetic Scattering; Admittance; Permeability; Image of Chiral Material; Scattering From Chiral Cylinders Above a Ground Plane